2022
DOI: 10.1186/s13054-022-04195-7
|View full text |Cite
|
Sign up to set email alerts
|

An area under the concentration–time curve threshold as a predictor of efficacy and nephrotoxicity for individualizing polymyxin B dosing in patients with carbapenem-resistant gram-negative bacteria

Abstract: Background Evidence supports therapeutic drug monitoring of polymyxin B, but clinical data for establishing an area under the concentration–time curve across 24 h at steady state (AUCss,24 h) threshold are still limited. This study aimed to examine exposure–response/toxicity relationship for polymyxin B to establish an AUCss,24 h threshold in a real-world cohort of patients. Methods Using a validated Bayesian approach to estimate AUCss,24 h from tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 35 publications
5
10
0
Order By: Relevance
“…Data from our prospective study indicated there was no correlation between whether ssAUC 0-24 met the criteria and clinical outcomes; however, the 28-day mortality in septic shock patients with a ssAUC 0-24 of polymyxin B between 50 and 100 mg ·h/L showed a decreasing trend, although not statistically significant due to limited sample size; also, AKI increased with increasing AUC, which is consistent with our previous findings in a real-world cohort of patients [ 24 ]. Septic shock is a severe subtype of sepsis with high mortality [ 25 ].…”
Section: Discussionsupporting
confidence: 89%
“…Data from our prospective study indicated there was no correlation between whether ssAUC 0-24 met the criteria and clinical outcomes; however, the 28-day mortality in septic shock patients with a ssAUC 0-24 of polymyxin B between 50 and 100 mg ·h/L showed a decreasing trend, although not statistically significant due to limited sample size; also, AKI increased with increasing AUC, which is consistent with our previous findings in a real-world cohort of patients [ 24 ]. Septic shock is a severe subtype of sepsis with high mortality [ 25 ].…”
Section: Discussionsupporting
confidence: 89%
“…However, when AUC 0-24h, ss achieved ∼100 mg·h/L, the risk of nephrotoxicity also increased. This was consistent with the research by Yang et al (2022b ), in which AUC 0-24h, ss >100 mg/L·h was a significant predictor of AKI in critically ill patients. In addition, Yang et al reported that the trough concentration of 1.2–2.8 mg/L was another index similar to AUC 0-24h, ss of 50–100 mg·h/L (34).…”
Section: Discussionsupporting
confidence: 93%
“…Thus AUC/MIC ≥ 50 was set as the efficacy target, as well as the MIC range was set at 0.25–4 mg L -1 ( Satlin et al, 2020 ). Additionally, considering the nephrotoxicity, AUC ss, 24h >100 mg∙h∙L -1 was chosen as an upper limit of the efficacy target ( Wang et al, 2021 ; Yang et al, 2022 ). In order to take the different ALB levels into account, the data has been divided into three groups based on the clinical guidelines, including the ultra-low ALB level group (21.3–24.9 g L -1 ), the low ALB level group (25–34.9 g L -1 ), and the normal ALB level group (35 –41.5 g L -1 ).…”
Section: Methodsmentioning
confidence: 99%